2010
DOI: 10.1128/mcb.00878-10
|View full text |Cite
|
Sign up to set email alerts
|

Nbr1 Is a Novel Inhibitor of Ligand-Mediated Receptor Tyrosine Kinase Degradation

Abstract: Neighbor of BRCA1 (Nbr1) is a highly conserved multidomain scaffold protein with proposed roles in endocytic trafficking and selective autophagy. However, the exact function of Nbr1 in these contexts has not been studied in detail. Here we investigated the role of Nbr1 in the trafficking of receptor tyrosine kinases (RTKs). We report that ectopic Nbr1 expression inhibits the ligand-mediated lysosomal degradation of RTKs, and this is probably done via the inhibition of receptor internalization. Conversely, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…p62/SQSTM1 and NBR1 are ubiquitin-binding proteins that have been proposed to act as cargo receptors in the process of autophagy (Lamark et al, 2009). We showed previously that p62 and NBR1 associate with Spred2, a signalling inhibitor, to promote degradation of RTKs, whereas NBR1 on its own inhibits RTKs degradation (Mardakheh et al, 2009;Mardakheh et al, 2010). Here we show that Ack1 highly colocalises with p62/SQSTM1 in unstimulated cells (Fig.…”
Section: Ack1 Localises Within Ubiquitin-rich Compartmentssupporting
confidence: 62%
See 1 more Smart Citation
“…p62/SQSTM1 and NBR1 are ubiquitin-binding proteins that have been proposed to act as cargo receptors in the process of autophagy (Lamark et al, 2009). We showed previously that p62 and NBR1 associate with Spred2, a signalling inhibitor, to promote degradation of RTKs, whereas NBR1 on its own inhibits RTKs degradation (Mardakheh et al, 2009;Mardakheh et al, 2010). Here we show that Ack1 highly colocalises with p62/SQSTM1 in unstimulated cells (Fig.…”
Section: Ack1 Localises Within Ubiquitin-rich Compartmentssupporting
confidence: 62%
“…Recently, we reported that NBR1 functions in degradation of RTK (Mardakheh et al, 2009;Mardakheh et al, 2010). Specifically we showed that association of NBR1 with Spred2, a signalling inhibitor, promotes RTK degradation, whereas NBR1 on its own inhibits degradation.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, it is tempting to speculate that this region might have a similar role as the membrane-interacting JUBA domain of human NBR1, which is essential for NBR1 localization to the late endosomes. 29 We observed formation of Joka2-Joka2 dimers independently for NpJoka2 (Fig. 1) and for NtJoka2 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…[21][22][23][24] The p62 protein mainly facilitates the autophagic clearance of the aggregates of the ubiquitinated proteins, however, it is also capable of binding nonubiquitinated proteins such as, TRAF6, 25,26 ALFY 27 or Keap1. 21 The human NBR1 protein is larger than p62 and in addition to the three domains common for both proteins, such as N-terminal phox/Bem1p (PB1), ZZ-type zinc finger and C-terminal ubiquitin association domain (UBA), it also contains two coiled-coil regions (CC1 and CC2), an amphipathic helical domain (JUBA) capable of binding phosphatidylinositol-phosphates 28,29 and the functionally uncharacterized NBR1 domain conserved in all NBR1-like proteins. 30 The NBR1 protein interacts with p62 in a PB1-PB1 fashion, 31 but homodimerizes via its N-terminal CC region.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the ubiquitin binding domain of NBR1, the UBA domain, may be required for binding to peroxisomes. Recently, the JUBA domain (hereafter for simplicity referred to as the J domain) -a novel, membraneinteracting, amphipathic a-helix region preceding the UBA domain -was found to be necessary for binding to endosomes (Mardakheh et al, 2010). Hence, we wanted to test if the J domain is also required for peroxisome binding.…”
Section: Lir Motifs Of Nbr1 Are Required For Pexophagymentioning
confidence: 99%